The Importance of Epistemology When Defending a Doctoral Thesis - Daniel P. Ash (Grounded Theory Review: An International Journal)
This article sets out a conceptual discussion based on a lively epistemological debate that took place during a doctoral viva voce examination for a classic grounded theory (GT) study (an exploration of police behaviour during domestic abuse incidents). The discussion uncovered conflicts regarding how methodology is viewed from different research traditions, and the potential impact of this problem on how research (like classic GT) is received and understood by scholars from different research philosophical perspectives, such as positivism. It also revealed how challenging it is, for a novice researcher, to adequately convince others of the rigorous nature of classic GT without reference and comparison to the research philosophical ideas that underpin other research traditions, more broadly. I claim that research philosophy must be addressed more fully by classic GT scholars if they are to encourage the uptake of classic GT by more doctoral candidates.